Propertius 1.3: Sleep, surprise, and Catullus 64 - Robinson, M (Wiley, 2013)
Although previous scholarship has noted some verbal and stylistic allusions to Catullus in Propertius 1.3, the extent to which the poem offers a profound and detailed engagement with Catullus 64 has not been recognised. Through a close reading of the opening couplets, I hope to demonstrate the care, artistry and sophistication with which Propertius engages with Catullus 64, as he imitates and illuminates many of its key stylistic and intertextual features. I argue that this engagement with Catullus 64 is importantly programmatic, and that Propertius 1.3, like Catullus 64, is very much concerned with narrative authority and poetic control. This concern comes to the fore in Cynthia's speech at the close of the poem, and I hope to show through further close reading how its relationship to literature and art encourages us to question Propertius's portrayal of his relationship with Cynthia at this very early stage in the corpus.